Research on the Psychological Mechanisms in Juvenile Crime Profiling - Liang, Yuchen (International Journal of Social Sciences and Public Administration, 2024)
Constructing the psychological mechanisms underlying juvenile crime profiling involves a critical examination of the interplay between biological factors and social factors in shaping juvenile delinquent psychology. Genetics, neurochemistry, and brain development—key biological determinants-directly influence adolescent behavior. Meanwhile, imbalances in social factors, including family dynamics, educational systems, and societal culture, are pivotal in the genesis of juvenile delinquency. This study elucidates how the psychological mechanisms of paranoid ideation, violent inclinations, and antisocial conduct emerge through the confluence of biological and social influences, underscoring the significance of an interdisciplinary approach in criminal profiling and preventive strategies.